When higher education is possible but not desirable: Widening participation and the aspirations of Australian Indigenous school students. (August 2017) - Gore, Jennifer; Patfield, Sally; Holmes, Kathryn; Smith, Maxwell; Lloyd, Adam; Gruppetta, Maree; Weaver, Natasha; Fray, Leanne
Indigenous students remain vastly under-represented within higher education in Australia. While aspirations have been a key focus of the widening participation agenda, the aspirations of Indigenous students have largely been overlooked. Drawing on survey data collected as part of a mixed methods longitudinal study conducted with students in Years 3 to 12 ( n  = 6492) from New South Wales government schools, this study investigated the occupational and educational aspirations of 432 Indigenous school students. While we found that Indigenous and non-Indigenous students held similar occupational aspirations, Indigenous students were much less likely to aspire to attend university. Most starkly, high-achieving Indigenous students were significantly less likely to aspire to university than their high-achieving non-Indigenous peers. Given this evidence, we argue that both the possibility and desirability of higher education must be addressed if the widening participation agenda is to meet equity targets for Indigenous students.